Risk factors for nuchal cord entanglement at delivery. Issue 1 (3rd January 2018) - Nkwabong, Elie; Ndoumbe Mballo, Jacky; Dohbit, Julius Sama
Abstract: Objective: To identify nuchal cord risk factors. Methods: The present case–control study was carried out between December 2016 and April 2017 at two hospitals in Yaoundé, Cameroon. Singletons with a nuchal cord at delivery (case group) as well as the two neonates without a nuchal cord delivered immediately after each case (control group), all in cephalic presentation, were included. Undated pregnancies were excluded. The main variables studied were maternal age, parity, pregnancy duration at delivery, cord insertion site, cord length, delivery weight, and fetal sex. Results: A nuchal cord was present in 121 (6.0%) of 2015 singletons. The final analysis included 114 and 228 neonates in the case and control groups, respectively, with similar maternal age, parity, pregnancy duration, and delivery weight. Significant independent risk factors for nuchal cord formation were a cord length of 70 cm or more (adjusted odds ratio [aOR] 19.10, 95% confidence interval [CI] 8.63–42.04), a pregnancy duration of more than 42 weeks (aOR 7.43, 95% CI 1.46–37.21), marginal cord insertion (aOR 2.90, 95% CI 1.11–9.35), and a male fetus (aOR 2.14, 95% CI 1.16–7.74). Conclusion: Marginal cord insertion and post‐term pregnancy should be added to the list of known nuchal cord risk factors. Abstract : Independent risk factors for nuchal cord entanglement at delivery are a long umbilical cord, a post‐term pregnancy, marginal cord insertion, and a male fetus.